APPLICATION DESIGN TO IMPROVE THE QUALITY OF UNIVERSITAS NEGERI SURABAYA DORMITORY MANAGEMENT - Kolektus Oky Ristanto; Prima Vidya Asteria; Testa Adi Nugraha (P3I UMSurabaya, 2024)
Universitas Negeri Surabaya (Unesa) has 3 dormitory buildings, 1 general dormitory building, and 1 PGSD dormitory building. The appropriateness of dormitory management at Unesa still can be improved from the service administration and finance aspect. To overcome the problem, this research will discuss about the update of Unesa dormitory management from manual to modern with utilize information and communication technology. The designed and developed applications namely the SIM ASRAMA EDUNESA, its purpose to increase quality of dormitory management. SIM ASRAMA EDUNESA is designed based on Android so makes it easier for user to access wherever and whenever. This study use descriptive qualitative approach. Subject research involved the dormitory residents. As for collecting data, research instruments used questionnaire and Focus Group Disscussion (FGD). Research results indicates: (1) SIM ASRAMA EDUNESA has been produced based android application, (2) SIM ASRAMA EDUNESA has several advantages, including the SIM ASRAMA Edunesa based on android application and database management system (DBMS), user can check room availability and facility conditions via online whenever and wherever, user can do online registration via applications, and can do online payment via various application payment. (3) Response from SIM ASRAMA EDUNESA user shows an average score of 3.84 with category worthy for applied with minor repairs. (4) The average percentage 77.29% shows that dormitory management improvements get positive response from dormitory residents with potency of dormitory management performance still can improved again.